Transformasi Kompetensi Profesional Guru Melalui Supervisi Akademik Model Artistik di Kabupaten Pidie - Salminawati, Salminawati; Sariakin, Sariakin; Novita, Rita (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The purpose of this research is to determine how to enhance the professional skills of teachers at SDN Keune, Pidie Regency, through the application of an artistic model in academic supervision, as observed in teachers' abilities to develop lesson plans/modules and conduct teaching.Method – The research method applied is School Action Research (SAR), aimed at addressing issues related to teachers' abilities in developing lesson plans/modules, conducting teaching, and their professional competencies which are still low within the school environment, while simultaneously seeking solutions to resolve them. Three teachers were selected as research subjects due to their relatively low professional competency levels, with an average professional competency score of 62.44. The selected teachers are from grades II, IV, and V at SDN Keune, Pidie Regency. This research follows a four-stage cycle: planning, action, observation, and reflection.Findings – The artistic model of academic supervision effectively improved teachers' professional competence. Initially, lesson plans/modules were inadequate, scoring 70.83 in Cycle I and improving to 86.11 in Cycle II. Teacher performance in lesson delivery scored 73.81 in Cycle I, rising to 86.90 in Cycle II. Professional competence increased from 71.67 in Cycle I to 88.33 in Cycle II. Research Implications – School supervisors play a crucial role in enhancing teachers' professional competencies through academic supervision. However, this study is limited in its applicability beyond SDN Keune and may be influenced by the researcher's biases in interpreting qualitative data and observations. Additionally, the focus on a small number of teachers limits the generalizability of the findings. Future research should consider a larger sample size and a more diverse range of schools to validate and expand upon these findings.